2017
DOI: 10.5530/jyp.2017.1s.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera Leaves Extract Against Hematology and Blood Biochemical Value of Patients with Iron Deficiency Anemia

Abstract: Introduction: Approximately (24.8%) the world's population suffers from anemia and 50% of an anemic case is due to iron deficiency. This study investigated the efficacy of Moringa oleifera L leaves to extract as an iron booster and supplement to help overcome anemia in the community. Methods: It was a randomized, double-blind, placebo-controlled study in anemic women (hemoglobin 8-12g/dL), in which the water extract of moringa leaves was examined as an add-on therapy in the subject treated with ferrous sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 8 publications
3
24
1
4
Order By: Relevance
“…This study disagrees with the results of Suzana et al (2017) that the Moringa leaves extract could improve iron deficiency anemia in women, and Tessera et al (2015) who reported that 5% Moringa leaves powder blended cookies have a potential to supply 53.6% of Fe to satisfy the RDA (9 mg/day) required by lactating mothers. In general, it might have a possibility to contribute better Fe content for lactating mothers to combat Iron deficiency problems.…”
Section: The Effect Of Medicinal Herb On Broiler Meats (Ucontrasting
confidence: 55%
“…This study disagrees with the results of Suzana et al (2017) that the Moringa leaves extract could improve iron deficiency anemia in women, and Tessera et al (2015) who reported that 5% Moringa leaves powder blended cookies have a potential to supply 53.6% of Fe to satisfy the RDA (9 mg/day) required by lactating mothers. In general, it might have a possibility to contribute better Fe content for lactating mothers to combat Iron deficiency problems.…”
Section: The Effect Of Medicinal Herb On Broiler Meats (Ucontrasting
confidence: 55%
“…The amount of Moringa consumed is also significant, since most mothers reported increasing the amount of Moringa they used in the third month after observing an improvement in their baby's health, which resulted to a sharp increase in Hb level afterward (Figure 3). Other studies conducted in India and Indonesia found a significant increase in Hb level among women who used M. Oleifera leaf extract (Sindhu, Mangala, & Sherry, 2013;Suzana et al, 2017). Moreover, the high content of vitamin A present in Moringa is an added advantage that contributed to the considerable reduction of anemia.…”
Section: Discussionmentioning
confidence: 93%
“…According to a report by Fahey (2005), even in places where Moringa has been used for many years such as India and some West African countries, most of the promotion of Moringa benefits are only focused on its medicinal benefits. Despite there being a lot of scientific evidence (Arise, Arise, Sanusi, Esan, & Oyeyinka, 2014;Babu, 2000;Busani et al, 2011;Oyeyinka & Oyeyinka, 2018) and feeding studies which have reported the nutritional potential of Moringa (Nambiar et al, 2012;Nurain, 2015;Srikanth, 2014;Suzana et al, 2017;Zongo et al, 2013), this knowledge is not tapped into poor countries that are highly affected by malnutrition. Therefore, sharing of best practices and study findings should not end in scientific, academic platforms such as journals and books, but more efforts should be invested to spread the information to the general public.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini sejalan dengan hasil penelitian Ponomban [7] yang menyatakan bahwa pemberian kapsul bubuk daun kelor selama 30 hari dapat meningkatkan kadar hemoglobin pada wanita hamil. Penelitian lain yang memberikan ekstrak air daun kelor sebanyak 1400 mg per hari selama 3 minggu pada wanita yang mengalami anemia defisiensi besi terbukti dapat meningkatkan kadar hemoglobin sebesar 0,794 ± 0,81 g/dL [15]. Selama penelitian terdapat 1 responden pada kelompok intervensi yang menyampaikan beberapa keluhan seperti pusing, kepala terasa berat dan merasa lemas.…”
Section: Pengaruh Pemberian Edukasi Dan Serbukunclassified